International strategic relations and China's national security. (International strategic relations and China's national security, 2018)
In 2016, economic globalization suffered a severe crisis after over half a century of smooth development, and deglobalization was running mountains high. It covers a wide range of important issues concerning international security, ranging from the assessment of Sino-US relations, Russian-American relations, the counter terrorism situation in the Middle East, the political situation in Taiwan and cross-Strait relations, Brexit and the refugee problem, and the strategic situation in the South China Sea, to the judgment of the strategic posture in countries and regions like Japan, the Korean Peninsula, Southeast Asia, Latin America and Africa.